2023
DOI: 10.3390/diagnostics13081423
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adding Digital Breast Tomosynthesis to BI-RADS Categorization of Mammographically Equivocal Breast Lesions

Abstract: Digital mammography (DM) is the cornerstone of breast cancer detection. Digital breast tomosynthesis (DBT) is an advanced imaging technique used for diagnosing and screening breast lesions, particularly in dense breasts. This study aimed to evaluate the impact of combining DBT with DM on the BI-RADS categorization of equivocal breast lesions. We prospectively evaluated 148 females with equivocal BI-RADS breast lesions (BI-RADS 0, 3, and 4) with DM. All patients underwent DBT. Two experienced radiologists analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…While diagnostic imaging is the mainstay in curative and screening protocols, digital breast tomosynthesis (DBT) offers better detection rates by reconstructing a pseudo threedimensional digital mammography thin section series from low-dose X-ray projections from different angles [3]. The advantage of DBT over "classical" 2D mammography is the reduction in the interference between regular breast tissue and possibly obscured tumors [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While diagnostic imaging is the mainstay in curative and screening protocols, digital breast tomosynthesis (DBT) offers better detection rates by reconstructing a pseudo threedimensional digital mammography thin section series from low-dose X-ray projections from different angles [3]. The advantage of DBT over "classical" 2D mammography is the reduction in the interference between regular breast tissue and possibly obscured tumors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an increased detection rate for breast cancer by adding DBT to conventional 2D mammography [4][5][6].…”
Section: Introductionmentioning
confidence: 99%